Personalized non-invasive neuromodulation for sensory-based urge suppression in individuals with OCD: a proof-of-concept investigation - Eng, Goi Khia; Tambini, Arielle; Hermiller, Molly S.; Recchia, Nicolette; Harvey, Jeanmarie R.; Iosifescu, Dan V.; Tobe, Russell H.; Stern, Emily R. (Frontiers in Human Neuroscience, 2025)
Obsessive-compulsive disorder (OCD) is chronic and impairing. While OCD often involves fear of harm or bad events, many patients experience “sensory phenomena,” which are aversive sensory experiences that drive repetitive behaviors regardless of specific fears. Standard treatments do not effectively address sensory phenomena, and novel approaches are needed. Transcranial magnetic stimulation (TMS) is a safe and non-invasive neuromodulation technique increasingly used in psychiatric disorders, including OCD. This work presents a data-driven approach to identifying TMS brain targets for modulating sensory urges in OCD incorporating both behavioral and clinical criteria (Study 1) for a proof-of-concept investigation (Study 2). Study 1 included 69 individuals with OCD and 23 controls who completed an urges-for-action fMRI task involving instructed eyeblink suppression as an experimental model for sensory-based urges. Data-driven conjunction analysis revealed several brain regions, including the right postcentral gyrus, that were associated with more blink suppression failure (behavioral), more severe sensory phenomena (clinical), and were hyperactivated in OCD patients compared to controls. Study 2 administered single-session inhibitory TMS on 4 returning OCD patients using individualized targets within the postcentral gyrus identified from Study 1. Compared to sham, inhibitory TMS delivered to individualized postcentral gyrus targets resulted in fewer blink suppression failures, reduced activation in the target (postcentral gyrus) and key urge-related areas (insula, mid-cingulate), and greater reduction in self-reported urge to engage in OCD-related compulsions, with medium to large effect sizes. These findings demonstrate the potential of utilizing data-driven approaches incorporating behavioral and clinical criteria to target hard-to-treat sensory phenomena in OCD.